The influence of preterm birth on expressive vocabulary at the age of 36 to 41 months. Issue 6 (February 2019) - Brósch-Fohraheim, Nina; Fuiko, Renate; Marschik, Peter B.; Resch, Bernhard
Abstract : Abstract: Children born preterm (PT) have a higher risk of language delays than children born full-term (FT). Expressive vocabulary plays a central role in language development, as later grammar ability can be predicted from earlier vocabulary size. To determine the effects of preterm birth on expressive vocabulary at the age of 36 to 41 months. Cross-sectional study of 27 PT (children with a gestational age of ⩽ 32 + 0 weeks and/or a birth weight ⩽ 1500 g) and 26 FT children (from several kindergartens in Vienna, Austria). The groups were matched regarding age, sex, and monolingual Austrian German speech. They were all examined using the active vocabulary test (AWST-R) and the development test, Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III). The AWST-R revealed significantly lower scores (46% vs 52%, P   =  .027) for PT children. The Bayley-III revealed significantly lower scores in language development (mean 96.3 ± 11.81 vs 105.1 ± 6.24, P   =  .002 ) and the expressive communication subscale (8.78 ± 2.01 vs 10.69 ± 1.49, P   <  .001) for PT children, but no differences in cognitive development (98.5 ± 11.08 vs 100.8 ± 6.43, P  = .369) or on the receptive communication subscale (10.15 ± 2.23 vs 11.08 ± 1.09, P  = .060). Preterm children tested had less expressive vocabulary (AWST-R and Bayley-III) than those born full-term, while test results in their cognitive development and receptive communication (Bayley-III) did not differ.